The Effect of the GISTEM Learning Model (Guided Inquiry, Science, Technology, Engineering, And Mathematics) on Students’ Problem Solving Ability on Sound Wave Material - Maryani, Elsa; Ridwan, Irwan Muhammad; Nana, Nana (Universitas Negeri Padang, 2025)
This research was motivated by the low problem-solving abilities of students on sound wave material and the need for more innovative approaches in physics learning. To address this issue, the GISTEM learning model (Guided Inquiry, Science, Technology, Engineering, and Mathematics) was implemented. The research used a quasi-experimental method with a Pretest-Posttest Control Group Design. The population consisted of 216 students from six class XI Phase F physics specialization classes at SMAN 13 Garut. The sample was selected using a Cluster Random Sampling technique, with class XI-12 as the experimental group and class XI-11 as the control group, each consisting of 36 students. Problem-solving skills were measured using 10 descriptive test items administered as pretest and posttest. Data analysis involved prerequisite tests (normality and homogeneity), t-test hypothesis testing, and calculation of learning gains. The hypothesis test using the t-test at a significance level of α = 0.05 showed that (15.56 > 1.67). Therefore, Hₐ was accepted, and H₀ was rejected. These results indicate that the GISTEM learning model significantly affects students’ problem-solving skills on sound wave material. The effectiveness of this model is attributed to its ability to promote independent learning, support conceptual understanding, and encourage the application of knowledge in new contexts.